KEMAMPUAN PENALARAN SISWA SMP DALAM MENYELESAIKAN SOAL LITERASI MATEMATIKA PADA SISWA TIPE ADVERSITY QUOTIENT (AQ) - F.X. Didik Purwosetiyono; Meisy Rahma Putri Budiyanti; Rizky Esti Utami; Achmad Buchori (FKIP, Universitas Palangka Raya, 2022)
This study describes students' mathematical reasoning abilities to solve mathematical literacy questions on adversity quotient (AQ) type students qualitatively. The researcher collected data from VIII-H class students at SMP Negeri 1 Gemuh, totaling 31 students using purposive sampling with the help of the mathematics teacher's consideration of where to conduct the research. The subjects selected in this study consisted of 6 subjects, namely two subjects with AQ quitters (low), two types of AQ campers (medium), and two types of AQ climbers (high). Data collection techniques used Adversity Response Profile (ARP) questionnaire instruments, written tests, documentation. The analysis technique is done by reducing data, presenting data, and drawing conclusions. Data validity checking techniques use technical and source triangulation. The results showed that 1) students with the AQ climbers type gave rise to five indicators of mathematical reasoning, namely making conjectures, manipulating mathematics, determining patterns to make generalizations, compiling evidence or reasons for correct solutions, and drawing conclusions. 2) students with AQ type campers bring up four indicators of mathematical reasoning, namely making conjectures, doing mathematical manipulation, determining patterns to make generalizations, and drawing conclusions. 3) students with the AQ quitter type are only able to bring up two indicators of reasoning, namely making conjectures and manipulating.